The Implementation of Noble Character Education at the Ummul Qur’an Islamic Boarding School - Prayitno Prayitno; Wakib Kurniawan; Susi Herawati (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Character education is of paramount importance as it plays a crucial role in shaping individual personality, preventing social problems, and preparing future generations to become responsible members of society equipped with essential life skills for social interaction. The purpose of this study is to examine the values underlying the implementation of noble character education applied at Ummul Qur’an Islamic Boarding School in Kediri, with the aim of providing knowledge and understanding to all stakeholders, including teachers, parents, and students, as well as contributing to the development of educational science and scholarly discourse. This study employs a qualitative research method with a descriptive approach, seeking to understand phenomena from the participants’ perspectives by emphasizing meaning, experience, and contextual factors. Data were collected through interviews, observations, and documentation. The research involved five informants, namely the head of the boarding school, teachers (ustadz), students (santri), a security officer, and a kitchen staff member. The findings indicate that Islamic boarding schools play a significant role in shaping students’ character through habituation, exemplary behavior, and the internalization of religious values. Ummul Qur’an Islamic Boarding School in Kediri implements a character education program consisting of 29 noble character values, aimed at ensuring that students are not only academically competent but also possess commendable moral character